Functional diversity: towards a new paradigm in disability studies and disability policies - Toboso Martín, Mario (Política y Sociedad, 2018)
In this paper we propose the development of “functional diversity paradigm” as a new approach applicable to the general theme of disability, both in its epistemic and political dimensions. Firstly, we carry out the re-evaluation of the currently dominant paradigm in Disability Studies, involving the hybridization of two explanatory models, the so-called “medical model” and “social model”. The aim of the new paradigm focus on the resolution of the explanatory anomalies of the aforementioned mixture of models and offer a new conceptual framework in the academic and political realms, in order to promote the conditions for a necessary change in relation to the social interpretation of disability. We propose that functional diversity paradigm brings together the following elements: diversity model related to Amartya Sen’s capabilities and functionings approach, reintroduction of the body through bioethics, diversity ethics as a critical perspective against ableism, abandonment of ability through the elaboration of a notion of functioning according to the concept of functional diversity and the notion of functioning ecosystems. The reinterpretation of disability as a form of human diversity inspires the 2006 UN Convention on the Rights of Persons with Disabilities, one of his general principles states: “Respect for difference and acceptance of persons with disabilities as part of human diversity and humanity”.